PENGEMBANGAN MEDIA KARUNCA (KARTU UNO PERKALIAN CERDAS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS III SD NEGERI SINDURJAN - Ulfah Rully Alif Nabila; Titi Anjarini; Rintis Rizkia Pangestika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to (1) develop the KARUNCA (Smart Multiplication UNO Card) learning media, (2) determine the feasibility of the KARUNCA media, and (3) examine its effectiveness in improving students' learning motivation and learning outcomes on multiplication as repeated addition for third-grade students at SD Negeri Sindurjan. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects comprised 18 students, including 5 students in the limited trial and 13 students in the large-scale trial. Data were collected through observation, interviews, questionnaires, and pretests and posttests. The results indicated that the KARUNCA learning media was highly feasible, as demonstrated by validation scores of 98% from the material expert, 98% from the media expert, and 94% from the teacher practitioner. Students' responses reached 92%, categorized as very good, while students' learning motivation achieved an average score of 90%, indicating an effective category. The effectiveness of the media was demonstrated by the N-Gain scores, with an average of 0.67 (moderate category) in the limited trial and 0.70 (moderate category) in the large-scale trial, indicating that the media was moderately effective in improving students' learning outcomes.